(untitled) (Conferencea, 2024)
The textile industry, particularly the segment focused on yarn production, is experiencing transformative changes fueled by technological advancements and in-depth research. These developments aim to optimize various production parameters and improve the overall quality of yarn. This paper analyzes recent research findings that explore critical factors influencing yarn quality, such as spindle speed, the aerodynamic properties of cotton fibers, yarn tension, and the implications of technological processes on both semi-finished and finished products.